Seroprevalence of dengue infection in pregnant women and placental antibody transfer - Nujum, Zinia T. (Med J Armed Forces India, 2019)
BACKGROUND: Pregnant women and infants are vulnerable for developing severe dengue. This study was conducted to determine the seroprevalence of dengue infections among pregnant women, their offsprings and its association with outcomes. METHODS: A cross-sectional study was conducted among pregnant women, admitted for delivery in a tertiary mother and child hospital in Thiruvananthapuram. Blood specimens (2 ml) were collected from the women during hospitalization in the first stage along with blood samples being drawn for other investigations. Umbilical cord blood was collected from the neonates. The samples were tested using IgG enzyme-linked immunosorbent assay (ELISA). Quantitative titres were also obtained, and index ratios were calculated using optical density values. RESULTS: Seroprevalence of dengue in antenatal women was 6.9% (95% confidence interval [CI]: 3.4–12.48). Among cord blood samples, the seropositivity was 10.8% (95% CI: 6.3–16.6). A significant correlation (Spearman rho: 0.653 and p value <0.001) was obtained between maternal and cord sample IgG index ratios. Agreement between maternal and cord blood IgG values was obtained using kappa as 0.742. The mean weight of newborns born to IgG-positive mothers was significantly lower than babies of IgG-negative mothers (2.3 vs 2.8; t = 2.64; p = 0.01). The mean gestational age at delivery was also significantly lower in IgG-positive mothers (36.29 vs 38.04 weeks; t = 2.48; p = 0.01). CONCLUSION: Seroprevalence of dengue in antenatal women and in their offsprings is lower than other areas endemic for dengue. Dengue infection (any time before pregnancy) may result in preterm delivery and low birth weights.